CYTOLOGICAL EFFECTS OF PULSED ELECTROMAGNETIC FIELDS AND STATIC MAGNETIC FIELDS INDUCED BY A THERAPEUTIC DEVICE ON IN VIVO EXPOSED RATS. - Rodriguez de la Fuente, Abraham Octavio; Heredia-Rojas, Jose Antonio; Carranza-Rosales, Pilar; Heredia-Rodriguez, Omar; Lozano-Garza, Gerardo; Zavala-Pompa, Angel; Rodriguez-Flores, Laura E. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: There is a trend towards the use of magnetic fields in medicine. Pulsed electromagnetic fields (PEMFs) technology was basedupon 20 years of fundamental studies on the electromechanical properties of bone and other connective tissues. More recently, these magneticfields have been used to treat several health conditions. There remains continuing concern that exposure to electromagnetic devices may causeadverse effects. The aim of the present study was to investigate the cytological effects induced in rats exposed in a patented medical device thatuses PEMFs combined with static magnetic fields (SMFs).Material and Methods: Thirty sexually mature 14-week-old male and female Sprague Dawley rats were distributed into three groups: (a) 5males and 5 females (independently) exposed to PEMFs combined with SMFs, (b) animals treated with SMFs only, and (c) non-exposedanimals. Acridine orange fluorescent-staining micronucleus test and male germ cells analysis were performed according to standardizedtechniques.Results: A lack of evidence for alterations on micronucleus frequency, on polychromatic erythrocytes percentage, and on sperm counts andmorphological characteristics of male germ cells were found in mature rats exposed to PEMFs medical device compared to non-exposedanimals.Conclusions: This study suggests that the applied magnetic field generated in a therapeutic device did not have any detectable cytotoxic orgenotoxic effect in exposed rats. In view of these findings and the contradictory reports in the literature, it is necessary to carry out moreresearch to help clarify the controversy concerning cytogenotoxic risk associated with therapeutic magnetic fields exposures.